2016
DOI: 10.5194/amt-9-1025-2016
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution of particle-associated polybrominated diphenyl ethers (PBDEs) and their implications for health

Abstract: Abstract. In order to better understand the size distribution of particle-associated PBDEs and their deposition pattern in the human respiratory tract, we carried out a 1-year campaign during 2012-2013 for the measurement of sizeresolved particles at the urban site of Shanghai. The results showed that particulate PBDEs exhibited a bimodal distribution with a mode peak in the accumulation particle size range and the second mode peak in the coarse particle size ranges. As the number of bromine atoms in the molec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 72 publications
(69 reference statements)
1
13
0
Order By: Relevance
“…S2). Analogous trends have also been observed for PBDEs (Besis et al 2015;Luo et al 2014;Lyu et al 2016;Mandalakis et al 2009;Okonski et al 2014) and other classes of organic contaminants (Chrysikou and Samara 2009;Landlová et al 2014). BDE-209 exhibited a different size distribution pattern (Fig.…”
Section: Particle-size Distribution Of Pbdessupporting
confidence: 71%
See 1 more Smart Citation
“…S2). Analogous trends have also been observed for PBDEs (Besis et al 2015;Luo et al 2014;Lyu et al 2016;Mandalakis et al 2009;Okonski et al 2014) and other classes of organic contaminants (Chrysikou and Samara 2009;Landlová et al 2014). BDE-209 exhibited a different size distribution pattern (Fig.…”
Section: Particle-size Distribution Of Pbdessupporting
confidence: 71%
“…Luo et al (2014) reported positive correlation between mass fractions in coarse particles and the log P L°f or trito hexa-BDEs, and a negative correlation for hepta-to deca-BDEs. Also, Lyu et al (2016)…”
Section: Particle-size Distribution Of Pbdesmentioning
confidence: 99%
“…PM with aerodynamic diameters <2.5 µm (PM 2.5 ) can penetrate deep inside the lung’s gas exchange region, while larger sized PM may reside in the head or tracheobronchial region of the respiratory tract [ 32 ]. Lyu et al (2016) [ 33 ] collected size-resolved air particulates (<0.4 to >9.0 µm) at an urban site in Shanghai, China, between 2012 and 2013. Deposition fluxes indicated that only 11% of the PBDE-laden particles would likely enter the alveolar region.…”
Section: Resultsmentioning
confidence: 99%
“…In the perspective of health scenarios, the long-term exposure of FRs may have built a greater potential for the adverse health effects on living organisms as compared to short-term exposure for FRs (Lyu et al, 2016). The ingestion and inhalation of FRs could be carried out via dust or aerosol in air.…”
Section: Introductionmentioning
confidence: 99%